Pengaruh Knowledge Sharing Terhadap Performance Dosen Dengan Kerja Tim Dan Inovasi Sebagai Variable Intervening Pada Universitas Majalengka - Rita Sri Silvia Pamuji; Lili Karmela; Dede Djuniardi (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2023)
The knowledge sharing process is shown by the willingness of individuals in the organization to receive and disseminate information, knowledge and skills they have, how it affects lecturer performance with teamwork and innovation as intervening variables at Majalengka University. One of the study programs at Majalengka University has decreased SKP scores for the last 3 (three) years, namely the School Teacher Education Study Program Basic as a gap phenomenon, there is also a research gap, Rista Ramadhan Tri Wahyuni and Anang Kiatyanto (in 2013), and Danang Firmaiansyah (in 2014) stated that knowledge sharing has an influence on performance, according to research conducted by Salih Yesil, Alaedin Koska, Tuba Buyukbese (in 2013) showed that the results of knowledge sharing have no influence on performance. The next difference lies in the different research locations and fields. The method used a descriptive method with a quantitative approach, using questionnaires distributed through google forms. The research technique uses a Structural Equation Model (SEM) based on Partial Least Square (PLS). The results showed that the influence of knowledge sharing on lecturer performance had no effect. The relationship of knowledge sharing to teamwork has an influence. Knowledge sharing on innovation has an influence.The results of indirect testing state that teamwork is able to mediate the relationship between knowledge sharing and lecturer performance, in contrast to when mediated by innovation, it turns out that innovation is not able to mediate the influence of knowledge sharing relationships on lecturer performance. Although the sharing of high knowledge carried out by Majalengka University does not affect the performance of lecturers, it is different if it is intervening with teamwork.